Sacred Space - Pamela Adelstein MD (SAGE Publishing, 2018)
A space can be sacred, providing those who inhabit a particular space with sense of transcendence-being connected to something greater than oneself. The sacredness may be inherent in the space, as for a religious institution or a serene place outdoors. Alternatively, a space may be made sacred by the people within it and events that occur there. As medical providers, we have the opportunity to create sacred space in our examination rooms and with our patient interactions. This sacred space can be healing to our patients and can bring us providers opportunities for increased connection, joy, and gratitude in our daily work.